Atomic-Orbital and Plane-Wave Approaches to Ferromagnetic Properties of NixFe1-x Nanowires. (7th February 2017) - Ziti, Ikram; Britel, M. R.; Wang, Chumin
ABSTRACT: There are growing interests on magnetic nanowires, due to their potential applications in magnetic sensors and recording devices. In this work, we report a comparative ab-initio study based on the Density Functional Theory (DFT) of Ni x Fe1- x nanowire periodic arrays by using atomic-orbital and plane-wave basis respectively through DMol 3 and CASTEP codes. After performing the geometry optimization, we calculate the spin-polarized electronic density of states, average interatomic distance, and magnetic moments. For pure Ni nanowires (x = 1, the dependence of the magnetic moment obtained from CASTEP calculations on the cutoff energy, as well as that from DMol 3 on the thermal smearing parameter is analyzed in detail. Both ab-initio calculations predict close magnetic moments for each x, being slightly larger those of DMol 3 obtained with significantly less computing cost. Finally, these DFT results are compared with experimental data and a good agreement is observed.